Beberapa Faktor yang Berkaitan dengan Praktek Kepala Keluarga Dalam Membuang Limbah Rumah Tangga di Kelurahan Bendanduwur Kecamatan Gajah Mungkur Kota Semarang. - Kusyogo Cahyo; Sri Sumarni (Jurnal Kesehatan Lingkungan Indonesia, 2015)
ABSTRACT Background : The poluted river is still a problem in a big city, for example Kali Garang, which is used by Water Drinking District Company in producing portable water in Semarang City. The stream zone of Kali Garang trought the crowded people areas/houses, where people still use water from Kali Garang for daily need, include domestic waste, It caused the quality of water in Kali Garang trend to decrese. The aims of this research is to know some faktors related to the practise of the head of family (house wife) in disposing domestic waste. The factors are education, knowledge, attitude, waste domestic tools and family environment. Methods : This was an explanatory research, using survey method with cross-sectional design. The data would be analized using Chi-Square method at 0,05 level of significant. Results : This research show that the relationship between education, knowledge, attitude, waste domestic tools and family environment with the practise of the head of family in disposing domestic waste are significant. Key Words : Domestic Waste Diposal, The Head of Family, Semarang